Growth and properties of co-evaporated Cu2SnS3 thin films for solar cell applications. (September 2016) - Chalapathi, U.; Poornaprakash, B.; Park, Si-Hyun
Abstract: Cu2 SnS3 (CTS) is a promising candidate for thin film solar cells due to its suitable optical and electrical properties. In this paper, we report the growth of CTS thin films by co-evaporation of Cu, Sn and S onto soda-lime glass substrates held at 350 °C. The effect of annealing temperature on the growth and properties of these films is investigated by studying their structural, microstructural, optical and electrical properties using appropriate characterization techniques. XRD and Raman analyses revealed that the co-evaporated films contain CTS, CuS and Cu4 SnS4 phases. On annealing these films at 520 °C for 10 min, Cu1.9375 S emerges as a secondary phase, CTS being dominant phase. Further increase in the annealing temperature from 550 °C−580 °C leads to the elimination of Cu1.9375 S phase completely. The films are found to be near-stoichiometric and polycrystalline CTS with monoclinic structure having ( 1 ¯ 31)/(200) preferred orientation. The crystallite size of the annealed CTS films is found to be 70 nm. The surface morphology of the films annealed at 550 °C for 10 min is found to be compact with grain size in the range 100 nm−500 nm. The direct optical band gap of these films is found to be 0.97 eV. Highlights: Growth of Cu2 SnS3 thin films by co-evaporation followed by annealing. Effect of annealing temperature on the growth of Cu2 SnS3 thin films. X-ray diffraction and Raman spectroscopy analyses for phase identification.